Karyotype of apomictic Dandelion (Taraxacum officinale), a wild plant with high medicinal value - Sajjad Hussain2**, Arshid Andrab3, Bashir Ahmad Wafai3, Khali Majid Fazili1*, Yousuf Ali2, Syed (Recent Research in Science and Technology, 2011)
Taraxacum officinale (Dandelion) includes sexually diploid as well as apomictic polyploid, mostly triploid plants. Apomixis holds great promise in agriculture and biotechnology as it fixes traits regardless of their complexity in genetic control.Ã‚Â Taraxacum officinale serves as a model system to investigate the genetics, ecology and evolution of apomixis. The Taraxacum seeds were allowed to germinate, The colchicine treated metaphasic cells of the dividing root tips were fixed, and processed for chromosome analysis. It is found that Taraxacum officinale of Kashmir is a triploid (2N=3X=24), based on X=8. The karyotyping reveals symmetrical karyotype of the genus where in centromere is metacentric in six triplets and sub-metacentric in two triplets.